Urbanität und Dichte im Städtebau des 20. Jahrhunderts - Sonne, Wolfgang 1965- (DOM-publishers, 2014)
On the basis of plans, systems, and theories of dense and urban cities of the 20th century, examples of urban planning are analyzed and highlighted. Addresses concepts that are essentially characterized by functional mix, social openness, public spaces, urban architecture, and urban culture. Best practice models are derived from current plans, different historical examples, and today's aspirations for urban density. -- Translated from book jacket